SERPIN A5 may have a potential as a biomarker in reflecting the improvement of semen quality in infertile men who underwent varicocele repair. (19th May 2021) - Teke, Kerem; Kasap, Murat; Simsek, Emrah; Uzunyol, Ayimgul; Uslubas, Ali Kemal; Akpinar, Gurler; Culha, Mustafa Melih
Abstract: We aimed to identify proteins that were differentially regulated in spermatozoal samples collected from fertile healthy men (FHM) and infertile patients with varicocele (IFPV) before and after varicocelectomy. Seminal samples were collected from 20 IFPV before and after varicocelectomy and from 14 FHM as controls. Samples underwent seminal examination and proteomic analysis. Extracted spermatozoal proteins were analysed using two‐dimensional gel electrophoresis, and differentially regulated spermatozoal proteins (DRSPs) were identified. In particular, attention was placed on those DRSPs in which the concentration changed after varicocelectomy and corrected to approximate levels observed in FHM. Varicocelectomy significantly improved the sperm count and concentration in IFPV ( p  < 0.05). Proteomic analysis showed that 11 DRSPs were identified when comparisons were made among the three groups. Among these 11 proteins, change in the SERPIN A5 concentrations was notable because it was 100‐fold downregulated in pre‐operative IFPV samples and nearly resembled to control concentrations following varicocelectomy. Western blot analysis using an anti‐SERPIN antibody validated the changes observed in SERPIN A5 levels before and after varicocelectomy operation. Increase in SERPIN A5 after varicocelectomy may be due to improvement in semen quality, suggesting that SERPIN A5 is a potential seminal biomarker for assessment of semen quality in varicocele‐related infertility.